World Bank Country Offices and Parliamentarians : A Survey - World Bank (Washington, DC, 2014)
Country offices engage with parliamentarians for several reasons. Parliamentarians pass laws and discuss, modify, approve or reject other legislation relevant for the World Bank Group (budget, development programs, etc). They provide oversight in sectors where the World Bank Group is active. They ratify World Bank loans and projects or in donor countries, they decide on International Development Association (IDA) contributions or capital increases and occasionally seek to influence World Bank policies. They allow the bank to have a broader perspective than that of the government alone: parliamentarians represent the communities that the World Bank assists. They are a strong expression of public opinion and are or can have a strong influence on key players of a country s development and reform agenda. The World Bank seeks to engage parliamentarians by providing information on development, strengthening the capacity of parliamentarians, and discussing World Bank policy, research and country work. Often, country offices are the main point of contact. At the end of 2009, the World Bank conducted a broad, informal survey of country offices relationships with parliaments. The survey explores the bank s interaction with parliamentarians at the country level, as well as challenges and opportunities for future interaction. Sixty-two respondents, representing 75 countries from all regions completed the survey.